Knowledge, attitude, and practice of techniques of breastfeeding among new mothers: A survey across Delhi Region - Himanshu Verma; Sirshti Singh; Nitika Bahuguna; Mukul Dahiya; Jyoti Shah (Wolters Kluwer Medknow Publications, 2022)
Objective: The present study aims to evaluate aims to assess the knowledge, attitude, and practice of primiparous mothers in the immediate postpartum period regarding breastfeeding techniques which will be helpful in forming awareness and training programs. Materials and Methods: A cross-sectional survey was used. A total of 120 primiparous mothers with a mean age of 24.92 years participated in the survey and filled the questionnaire related to the knowledge, attitude, and practice of techniques of breastfeeding. Results: Results revealed that 48.3% of new mothers were not aware of the correct techniques to initiate breastfeeding, whereas 68.3% of subjects reported that during latching, the baby's upper and lower lip should be everted. The majority of new mothers were aware of breastfeeding techniques with some misconceptions as in our culture, most of the breastfeeding information passed from generation to generation. Conclusion: The level of awareness about feeding skills among primiparous mothers can be further improved by antenatal counseling or training from health-care workers during the gestational period. This will further help new mothers to educate and will provide adequate information which will decrease the myths.